The Legal Consequences of Transferring Trade Secrets on Under Hand’s Scheme - Suhardin, Yohanes; Sitorus, Rolib; Khuan, Hendri; Manullang, Sardjana Orba (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Unauthorized transfer of trade secrets can harm the owner, cause financial loss, damage reputation and trigger legal action. In the era of globalization and technology, the transfer of trade secrets is increasingly urgent to be legally regulated. Legislation has been implemented in various countries to protect trade secrets, but the legal consequences vary. The repercussions involve financial loss, reputation, legal action and ethical business considerations.Purposes of the Research: The purpose of this study is to investigate and analyze the process of identifying and handling the transfer of trade secrets under the hand in Indonesian legal practice. This study also aims to understand the legal consequences that apply to the perpetrators of private transfer of trade secrets in the Indonesian legal system. Methods of the Research: This research uses normative legal research methods to analyze statutory regulations, court decisions, and legal literature related to the private transfer of trade secrets. A statutory approach helps understand the applicable legal framework. Data sources include various legal documents and legal literature, with data collection techniques focusing on document analysis and literature study. Data analysis involves identifying trends and legal implications of cases related to private transfer of trade secrets in the Indonesian legal context.Results of the Research: The process of identifying and handling illegal transfers of trade secrets in Indonesia is an important step in protecting business and industry. It covers the steps from identification to prosecution, with reference to regulations such as the Trade Secret Act. Trade secrets must be confidential and have economic value. Prevention through internal security policies and employee training is also necessary. Perpetrators of the transfer of trade secrets may face civil, criminal and administrative actions in accordance with applicable law, with consequences including criminal sanctions, demands for compensation and confiscation of goods or documents. Protection is also given to whistleblowers in good faith. Internal policies, nondisclosure agreements, and consulting legal advisors are important for protecting trade secrets. All parties must understand and comply with the law to maintain business integrity in Indonesia.